Adverse Effects of Grape Seed Extract Supplement: A Clinical Case and Long-Term Follow-Up. (3rd March 2016) - Berry, Andrew C.; Nakshabendi, Rahman; Abidali, Hussein; Atchaneeyasakul, Kunakorn; Dholaria, Kevin; Johnson, Cassandra; Kishore, Varsha A.; Baltz, Aaron C.
ABSTRACT : Grape seed extract (GSE) supplement use is becoming more popular today for its potential chemopreventive and chemotherapeutic role. We report a 49-year-old male who presented with recurrent nausea, vomiting, diarrhea, and acute weakness following GSE use. A thorough medical workup ensued and no causes were identified clinically, procedurally, or with imaging. Symptoms resolved after GSE discontinuation and the patient remained symptom-free 5 years later. This case illustrates the paucity of documented detailed clinical cases and lack of controlled trials detailing a thorough and reproducible adverse effect profile of GSE supplement.